Limnobium laevigatum (Hydrocharitaceae), new record for La Pampa province flora, Argentina (Semiárida, 2018)
This article reports the recording of Limnobium laevigatum (Hydrocharitaceae) for the first time ever in the province of La Pampa, Argentina. Specimens were collected from a surface rainwater drain of Ingeniero Luiggi town, and their presence gave way to a taxonomic novelty at the level of species, genus and family for the provincial flora. DOI: http://dx.doi.org/10.19137/semiarida.2016(01).25-27
Keywords: Hydrocharitaceae; hydrophytes; distribution; biodiversity